Persistent “MRI-negative” lupus myelitis-disease presentation, immunological profile and outcome - Das, Shambaditya; Ray, Biman Kanti; Chakraborty, Arka Prava; Banerjee, Abhirup; Pandit, Alak; Das, Gautam; Dubey, Souvik (Frontiers in Neurology, 2022)
INTRODUCTION: Myelitis is the least common neuropsychiatric manifestation in systemic lupus erythematosus (SLE). Magnetic resonance imaging (MRI)-negative myelitis is even rarer. Here, we present the largest cohort of MRI-negative lupus myelitis cases to assess their clinical and immunological profiles and outcomes. METHOD: A single-center, observational study conducted over a period of 5 years (2017–2021) was undertaken to evaluate patients with MRI-negative lupus myelitis for the epidemiological, clinical, immunological, and radiological features at baseline and followed up at monthly intervals for a year, and the outcomes were documented. Among the 22 patients that presented with MRI-negative myelopathy (clinical features suggestive of myelopathy without signal changes on spinal-cord MRI [3Tesla], performed serially at the time of presentation and 7 days, 6 weeks, and 3 months after the onset of symptoms), 8 patients had SLE and were included as the study population. . RESULTS: In 8 of 22 patients presenting with MRI-negative myelopathy, the etiology was SLE. MRI-negative lupus myelitis had a female preponderance(male:female ratio, 1:7). Mean age at onset of myelopathy was 30.0 ± 8.93 years, reaching nadir at 4.9 ± 4.39 weeks(Median, 3.0; range, 1.25–9.75). Clinically, cervical cord involvement was observed in 75% of patients, and 62.5% had selective tract involvement. The mean double stranded deoxyribonucleic acid, C3, and C4 titers at onset of myelopathy were 376.0 ± 342.88 IU/ml(median, 247.0), 46.1 ± 17.98 mg/dL(median, 47.5), and 7.3 ± 3.55 mg/dL(median, 9.0), respectively, with high SLE disease activity index 2000 score of 20.6 ± 5.9.Anti-ribosomal P protein,anti-Smith antibody, and anti-ribonuclear protein positivity was observed in 87.5%, 75%, and 75% of the patients, respectively. On follow-up, improvement of myelopathic features with no or minimal deficit was observed in 5 of the 8 patients (62.5%). None of the patients had recurrence or new neurological deficits over 1-year follow-up. CONCLUSION: Persistently “MRI-negative” lupus myelitis presents with white matter dysfunction, often with selective tract involvement, in light of high disease activity, which follows a monophasic course with good responsiveness to immunosuppressive therapy. A meticulous clinical evaluation and a low index of suspicion can greatly aid in the diagnosis of this rare clinical condition in lupus.